PERSEPSI GURU TENTANG PELUANG DAN TANTANGAN PEMBELAJARAN PKN DALAM MEWUJUDKAN KETERAMPILAN ABAD KE-21 SD NEGERI 3 RAJABASA - Mohammad Mona Adha; Muhammad Kaulan Karima; Mutiara Lesmanawati Pergiwa; Latifah; Tiara Farashinta; Alfian Deni Iskandar; Veronika Windy; Puji Larasati; Melisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores Civic and Pancasila Education teachers’ perspectives on the opportunities and challenges in implementing 21st-century skill–oriented learning. Employing a qualitative literature review approach, this research synthesizes various sources from books, journals, and earlier studies. Findings reveal that teachers generally acknowledge the importance of PPKn in fostering critical thinking, collaboration, communication, and creativity. Nevertheless, several challenges persist, including limited teacher readiness to apply technology, inadequate facilities, and teacher-centered instructional paradigms. The study highlights the need to enhance teachers’ pedagogical and digital skills, supported by school policies that encourage innovative learning.